Of mice and magic a history of American animated cartoons - Maltin, Leonard (New American Library, 1980)
In this revised and updated edition of Of Mice and Magic, Leonard Maltin not only recreates this whole glorious era from the silent days through the Hollywood golden age to Spielberg's An American Tail, he traces the evolution of the art of animation and vividly portrays the key creative talents and their studios. This definitive history of American animated cartoons also brings Maltin's many fans up to date on the work being done today at the Walt Disney and Warner Bros. studios, and other developments in the world of animation. Drawing on colorful interviews with many of the American cartoon industry's principals, Maltin has come up with a gold mine of anecdotes and film history. Behind the scenes were genius animators and entrepreneurs such as Walt Disney, Chuck Jones, Tex Avery, Mel Blanc, and a legion of others, In all, Malitn has put together a glorious celebration of a universally loved segment of Americana. Includes the most extensive filmography on cartoons ever compiled, and sources for video rental.